Optimalisasi Manajemen Madrasah dalam Meningkatkan Prestasi Belajar Siswa Melalui Kegiatan Ekstrakulikuler di MTs N 2 Deli Serdang - Rismoninta Padang; Makmur Syukri; Afrahul Fadhila Daulai (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to describe (1) to determine the Madrasah Management at MTs N 2 Deli Serdang in supporting and optimizing the implementation of extracurricular activities as an effort to improve student learning achievement (2) to determine the extent of the contribution of extracurricular activities to increasing student learning achievement at MTs N 2 Deli Serdang (3) to find out the obstacles faced by madrasas in managing extracurricular activities and how they affect student learning achievement. This research uses descriptive research with a qualitative approach. The subjects in the research were the Head of Madrasah, Deputy Head of Curriculum, Extracurricular Advisor and students. Data collection techniques using observation, interviews and documentation. Data collection analysis carried out data reduction, data presentation and drawing conclusions. And based on the results of research that researchers have conducted, extracurricular activities have run well in accordance with the planning, organization, implementation and supervision that the madrasah has carried out.